2001
DOI: 10.1051/0004-6361:20000332
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous H$\mathsf{\alpha}$ and photometric observations of P Cygni

Abstract: Abstract. For the first time an extensive set of (quasi-) simultaneous photometric (UBV ) and spectroscopic (Hα line profiles) observations of P Cygni, covering a period from May, 1990 to June, 1994 was analyzed in terms of time variability. It is found that the Hα equivalent width (EW ) exhibits two different patterns of variability: a slower one, called Long-Term (LT) variability, with an amplitude of about 30Å and a characteristic duration of about 600 days and a faster one, called Short-Term (ST) variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…The analysis by van Gent & Lamers (1986), on the other side, revealed 60-70 d but this was also based on scattered spectrocopy. Markova et al (2001a) found an anti-correlation between these 100 d-type oscillations and the equivalent width of the Hα emission line. Kolka (1999) discussed a 100 d-type cyclicity in the main spectroscopic features due to moving opacity enhancements (the DACs).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The analysis by van Gent & Lamers (1986), on the other side, revealed 60-70 d but this was also based on scattered spectrocopy. Markova et al (2001a) found an anti-correlation between these 100 d-type oscillations and the equivalent width of the Hα emission line. Kolka (1999) discussed a 100 d-type cyclicity in the main spectroscopic features due to moving opacity enhancements (the DACs).…”
Section: Discussionmentioning
confidence: 87%
“…5 and de Groot et al 2001). Support for this longer one is given by Markova et al (2001aMarkova et al ( , 2001b. They show that the Hα emission line is possibly cyclic on a time-scale of that order (∼7 y) and in phase with the brightness: maxima in 1985 (JD ∼ 2 446 300) and 1992 (JD ∼ 2 448 800), and minima in 1988 (JD ∼ 2 447 500) and in 1995 (JD ∼ 2 450 000).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The nature and origin of this kind of variability are still unknown. Recently, Markova et al (1998) have reported evidence for a LT variation in the brightness and temperature of P Cygni. The relationship between the LT wind variability and the LT photospheric variability (if any) is the subject of another study (Markova et al 2000a).…”
Section: Discussionmentioning
confidence: 99%